Settlement event satisfaction survey in the shade of the COVID epidemic - Slezák-Bartos, Zsuzsanna (Acta Cultura et Paedagogicae, 2023)
The settlement can be successful if the income in the settlement is constantly growing, new companies are settling down, giving jobs to the residents, as well as through cultural, entertainment opportunities and programs, the city management can provide meaningful pastimes for the local residents. The provision of cultural activities has a multifaceted impact on the development of the local economy. By developing or expanding the cultural capabilities, not only the quality of life of the local population can be improved, but also significant economic benefits can be achieved with proper organizational work. Although the crisis caused by the coronavirus epidemic poses a challenge to the economy, the tourism sector, city management and local cooperation need to continue the work started, services such as entertainment, sports, leisure recreation and cultural opportunities in the line with local preferences need to be expanded. The aim of the study is to find out the satisfaction of the people living in the Tolna county seat about the events and organized events. Moreover also looking for an answer how the popularity of Szekszárd wine region events among local residents changed as a result of the crisis caused by the coronavirus. Empirical research – by the opinions of local residents of Szekszárd, students and workers in the city - is based on online questionnaires, in-depth interviews and personal experiences.